2014
DOI: 10.4174/astr.2014.87.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thromboprophylaxis is sufficient to prevent the lower extremity deep vein thrombosis after kidney transplantation

Abstract: PurposeDeep vein thrombosis (DVT) is a severe and common complication that occurs after the major operation. Despite the commonality of DVT there is limited data on the incidence of DVT after kidney transplantation (KT). Furthermore, most studies have been retrospective in design and were conducted in western countries. The aim of this study was to evaluate the incidence of lower extremity DVT with mechanical thromboprophylaxis within 1 month of KT in Korea.MethodsA total of 187 consecutive patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To detect lower extremity deep DVT, we perform bilateral, whole-leg color duplex ultrasound on POD7, 14, and 28, or at any time when clinically indicated. [ 8 ] When bleeding is suspected (eg, suddenly decreased blood pressure and hemoglobin or bloody discharge in the Jackson-Pratt drains [Cardinal Health, Waukegan, IL]), we perform nonenhanced abdominal computed tomography to assess hematoma around the allograft kidney.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect lower extremity deep DVT, we perform bilateral, whole-leg color duplex ultrasound on POD7, 14, and 28, or at any time when clinically indicated. [ 8 ] When bleeding is suspected (eg, suddenly decreased blood pressure and hemoglobin or bloody discharge in the Jackson-Pratt drains [Cardinal Health, Waukegan, IL]), we perform nonenhanced abdominal computed tomography to assess hematoma around the allograft kidney.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic resonance angiography is performed on POD7 in cases with multiple donor renal arteries or suboptimal environments of the donor renal artery or recipient iliac artery, such as heavy calcifications or atheroma of the artery. To detect lower extremity deep DVT, we perform bilateral, whole-leg color duplex ultrasound on POD7, 14, and 28, or at any time when clinically indicated [8] . When bleeding is suspected (eg, suddenly decreased blood pressure and hemoglobin or bloody discharge in the Jackson-Pratt drains [Cardinal Health, Waukegan, IL]), we perform nonenhanced abdominal computed tomography to assess hematoma around the allograft kidney.…”
Section: Methodsmentioning
confidence: 99%
“…Kidney transplantation is categorised as a moderate risk group of patients for development of thromboprophylaxis conferring an estimated risk of DVT of 6% [38]. Limited studies have suggested the incidence to be lower with mechanical thromboprophylaxis alone [39]. Despite the lack of evidence, thromboprophylaxis Gastro-protection Ranitidine (or PPI) therapy while on high dose steroids…”
Section: Prophylactic Medicationsmentioning
confidence: 99%
“…Recent investigations of major cardiovascular events in solid organ transplant recipients have been limited largely by retrospective, single‐center data, mostly collected in the Western countries . However, ethnic disparity may play an important part in the risk of cardiovascular events among Asian organ transplant recipients . As Taiwan launched the National Health Insurance (NHI) Program in 1995, with nationwide coverage, the National Health Insurance Research Database (NHIRD) has nationwide representation, large size, and accurate data on diagnosis of cardiovascular events, organ transplant, cohort nature, and long‐term follow‐up, thus allowing the study of the risk of cardiovascular complications and mortality in Taiwanese organ transplant recipients.…”
Section: Introductionmentioning
confidence: 99%